Masalah yang dihadapi dalam penyediaan perumahan Polis Diraja Malaysia - Ismail, Azizee (2006)
In Malaysia, migration of population has increased the demand of houses especially in cities and big town. The high demand of houses have directly cause an increased in rental rate, which goes beyond the affordability of police personnel in general and they have to stay far away from their office and some of them rented houses in squarters area. The problem in providing housing to the police personnel has become a major agenda to the government. This situation occured because some of the police housing projects were delayed and abandoned. The aimed of this study is to identify the major problems that affected the achievement of the objective to provide ninety percent (90%) housing to the Royal Malaysia Police (RMP) personnel in the year 2000. The study will involved several RMP delayed and abandoned projects throughout Malaysia. In order to achieve the objectives identified, literature review was conducted and questionaire was distributed to contractors, consultants and Central Agency personnel. Upon receiving the feedbacks, the data was analyzed using an Average Index and translated with charts and tables. Findings had shown that situation occured because the contractor had failed to complete the project within the contract period. Some of these causes were due to financial problem and failure of the consultant to identify the root problems at earlier stage of construction. To overcome the problems, competence contractor with good track records; and excellent consultant along with personnel with technical knowledge; and appropriate qualification should be assigned to the project. With these consideration it helps to ensure that delay and failure in providing houses to Royal Malaysian Police personnel can be reduced